A market based composite political risk indicator for the international banking industry - Simpson, John (Centre for Research in Applied Economics, Curtin Business School, 2010)
The purpose of this paper is to test an international bank market pricing model, hypothesised to arrive at new indicator of pure composite political risk for country banking sectors. The motivation is that current political risk ratings (rating social, legal and cultural factors that impact political environments in countries) are largely subjectively quantified and are not frequently published. Political risk has not been a focus in media commentary to date on the global economic and financial spillovers of 2008/2009. An international capital asset pricing model for a banking system is useful as long as systemic interdependence, the degree of global integration, and country size and wealth can be controlled for as well as the impact on a country banking system of that country's stock market. The selected sample contains examples of country banking systems in developed and developing countries. The policy implications of the paper are that investors in banking portfolios, trade and investment policy formulators as well as banking regulators should be aware that it is possible that pure political risk indicators may be obtained as a daily management tool rather than monthly, from an analysis of international stock and banking market generated data.